Economic Cooperation among the OIC countries: a case of Turk-Malay Economic Cooperation - Kayadibi, Saim (2013)
This research tries to investigate bilateral relationship between the two sister countries in terms of economic cooperation. Although Turk-Malay relations goes back to the 13th century and have great deal of relationship in terms of cultural, political and social, the current economic cooperation is not the desired level. We emphasize that Turkey and Malaysia have steadily growing economic relations over the last decade; although the annual turnover is not as much as it should be, the increase is 994 million dollars in 2006 from a modest figure of 242 million dollars recorded in 2000 which makes Malaysia today the 7th largest trade partner for Turkey in the Far East. Furthermore, the trade volume exceeded 1.3 billion dollars with an increase by % 34 as against 994 million dollars in 2007. In spite of growing trade figures, the trade balance has long developed in favour of Malaysia. Turkey’s trade deficit amounted to 1.2 billion dollars with an increase by % 33 in comparison to the corresponding figures of the year 2009. Surprisingly Turkish exports to Malaysia had risen to $93 million with imports more than doubling to $498 million in 2010. It’s hoped that bilateral trade is expected to rise to $2.5 billion, with Malaysian exports making up a large portion in 2012. As Turkey and Malaysia are members of OIC countries, strategic partnership need to be developed bilaterally. For this, the Turkish Government has introduced initiatives like A Strategy to Improve Commercial and Economic Relations with Asia Pacific Countries; The Turkish and Malaysian Joint Economic Commission (JEC); The Turkish-Malaysian Business Council etc. This research will try to find ways to increase bilateral economic cooperation between the two sister countries of OIC. The objective of this research is to investigate how the two sister countries of OIC, Turk-Malay economic cooperation can be developed. The economic development would strength their cultural, social as well as their ummatic relationship which would be a model trade partner among the OIC countries. An expected result of this research would be to provide some ways to increase economic cooperation among the OIC countries especially between two sister countries Turkey and Malaysia. Methodology of the research is conducted to first collecting trade output of the two countries among them which involves in library sources, media sources and sources of the trade councils like Turkish and Malaysian Joint Economic Commission (JEC); The Turkish-Malaysian Business Council etc. The collected data will be inshaAllah critically analyzed accordingly in order to help to increase business cooperation of the two countries for the betterment of the Muslim Ummah. The Significance of this research is highly significant for its uniqueness and for providing ways to increase economic cooperation of the two sister countries of OIC. The expected research output is at least to highlight the importance of economic cooperation between OIC countries to strength their power in order to create better atmosphere and relationship among them that would open a way for the unity of Ummah Islam inshaAllah.